2016
DOI: 10.1179/2151090315y.0000000015
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of sagittal skeletal discrepancy, natural head position, and craniocervical posture in young Chinese children

Abstract: Significant differences exist in NHP and craniocervical posture among skeletal class I, II, and III relationships in young Chinese children. Subjects with skeletal class II relationship tended to exhibit more extended head, and children with skeletal class III relationship often exhibited flexed head.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 22 publications
3
11
0
8
Order By: Relevance
“…Solow and Tallgren found associations between craniofacial morphology and head posture [60], as well as Sharma et al have found [61]. Liu et al have described that subjects with skeletal class II patterns had a tendency to have a more extended head [62], with techniques of extension traction restoring lordosis in the cervical spine [63].…”
Section: Discussionmentioning
confidence: 89%
“…Solow and Tallgren found associations between craniofacial morphology and head posture [60], as well as Sharma et al have found [61]. Liu et al have described that subjects with skeletal class II patterns had a tendency to have a more extended head [62], with techniques of extension traction restoring lordosis in the cervical spine [63].…”
Section: Discussionmentioning
confidence: 89%
“…A cada uno se le realizó el cefalograma lateral y el análisis mediante el programa inf "Onyx Ceph", El objetivo de ese estudio fue examinar la relación entre la PC y los parámetros de la posición sagital, así como la longitud mandibular. Se demostró que el aumento de la extensión de la cabeza en relación con la columna cervical puede ser un factor que contribuye a la formación de una maloclusión clase II, concordando con los resultados de Sandoval (15) y Liu Y et al (19) .…”
Section: Discussionunclassified
“…Por su parte Liu Y et al (19) demostró además que los pacientes con alteraciones cráneo cervicales presentan mayor incidencia de maloclusiones clase III, extensión de la cabeza y un ángulo cráneo vertical aumentado. Este estudio tuvo como objetivo investigar las relaciones de discrepancia esquelética sagital, posición natural de la cabeza (PNC) y PCC en 90 niños chinos.…”
Section: Discussionunclassified
See 2 more Smart Citations